2019
DOI: 10.1055/a-0828-7541
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Paris Classification for superficial neoplastic gastric lesions improves with training and narrow band imaging

Abstract: Background and study aims Paris Classification is used to classify gastrointestinal superficial neoplastic lesions and to predict presence of submucosal invasion. We aimed to evaluate interobserver reliability and agreement for this classification among Western endoscopists. Methods A total of 54 superficial gastric lesions were independently classified according to Paris classification by eight endoscopists (4 experts and 4 non-experts). Observers were asked to classify two sets of images – first, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This revealed that polypoid type I (57 %) and types IIc (37 %) and III (40 %) had a higher risk of submucosal invasion. In comparison, forms IIa and IIb (29% and 20%) showed a lower probability of [5,29].…”
Section: Paris Classificationmentioning
confidence: 97%
“…This revealed that polypoid type I (57 %) and types IIc (37 %) and III (40 %) had a higher risk of submucosal invasion. In comparison, forms IIa and IIb (29% and 20%) showed a lower probability of [5,29].…”
Section: Paris Classificationmentioning
confidence: 97%
“…Since it is difficult to increase diagnostic accuracy using a single modality Cheng et al 72 Risk scores should be used to estimate the probability of noncurative resection, and this data can be shared with patients to help them make more informed decisions. 65,73 Some authors have proposed prediction models for noncurative resection of EGC. 74,75 Kim et al 74 analyzed 1639 patients who had undergone ESD for EGCs and 272 were identified as being noncuratively treated with ESD.…”
Section: How To Decrease Adverse Events?mentioning
confidence: 99%
“…Risk scores should be used to estimate the probability of noncurative resection, and this data can be shared with patients to help them make more informed decisions 65,73 . Some authors have proposed prediction models for noncurative resection of EGC 74,75 .…”
Section: How To Improve Patient Selection?mentioning
confidence: 99%
“…Kaise et al investigated depressed lesions using NBI and concluded that abnormality in vascular and mucosal pattern were specific for cancer but the reproducibility was only moderate (k=0.48) (89). Multiple studies have concluded NBI improves detection when compared to WLE (90,91). Meticulous examination of the mucosa pattern for irregular features is vitally important for detection of pre-malignant changes in clinical practice.…”
Section: Endoscopic Features Of Gastric Dysplasiamentioning
confidence: 99%
“…The Paris classification observer agreement is moderate to good. Training using this classification in combination with NBI improves accuracy of lesion detection and observer agreement (91). Both UK and international guidelines for the pre-malignant stomach recommend the use of high definition with image enhanced technology and where possible magnification.…”
Section: Endoscopy Assessmentmentioning
confidence: 99%